ANALISIS FAKTOR INTERNAL YANG MEMPENGARUHI PENDAPATAN PEER TO PEER LENDING(STUDI KASUS PADA PT.PASAR DANA PINJAMAN TAHUN 2018-2019) - Nurlis Azhar; Aldi Novrian Pambudi; Helmi Helmi; Nurwati Nurwati (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2023)
Peer-to-peer (P2P) lending has emerged as an innovative form of financing that provides individuals and businesses with access to much-needed funding. However, this online crowdfunding platform also carries inherent risks. This research aims to investigate the internal factors that impact P2P lending revenue, focusing on Non-Performance Loans, Fintech Adoption, Fintech Efficiency, Return on Assets (ROA), and Loan to Value (LTV) ratio. Utilizing a quantitative research methodology and data from reliable sources, this study employs statistical analysis using SPSS. The results of the T-test indicate that Non-Performance Loans and Return on Assets significantly influence Peer-to-Peer lending revenue. In contrast, Fintech Adoption, Fintech Efficiency, and Loan to Value Ratio do not have a significant impact on P2P lending revenue individually. Furthermore, the F-test demonstrates that when considered together, Non-Performance Loans, Fintech Adoption, Fintech Efficiency, Return on Assets, and Loan to Value Ratio collectively exert a significant influence on the revenue of PT. Pasar Dana Pinjaman, a company operating in the P2P lending and Fintech lending business